Corpus Analysis of Russian and English Resources in Vilnius Adolescents’ Speech - Vyšniauskienė, Inga (Taikomoji kalbotyra, 2014)
This paper presents the quantitative analysis of Russian and English resources in Vilnius adolescents’ language. The analysis draws on Vilnius Adolescents’ Language Corpus data, documenting the linguistic practices of 10–16 year old adolescents from differently socially and ethnically marked Vilnius neighbourhoods. The research has revealed strong correlation between ethnic marking of Vilnius neighbourhoods and both frequency as well as lexico-functional variation of Russian resources. Creativity, playfulness, situational strategic use of Russian resources characterize the language of adolescents from ethnically marked neighbourhoods. In contrast, Russian resources among adolescents in ethnically unmarked neighbourhoods have been limited to slang and swearing. In addition, Russian resources may correlate with such values as toughness and masculinity as they were twice more frequent among boys (from ethnically unmarked neighbourhoods) than girls. English resources are available to adolescents through computer-mediated communication, popular culture. Accordingly, the frequency of English resources and lexico-functional categories are similar among adolescents irrespective of the ethnic marking of the district. Generally, Vilnius adolescents’ practices of using Russian and English resources can hardly be described as one system. It is rather an open, dynamic interplay of different sub-systems having their internal organization, norms, which correlate with gender or ethnic marking of Vilnius neighbourhoods.